MAPPING THE LANDSCAPE OF GIG ECONOMY RESEARCH: A BIBLIOMETRIC ANALYSIS - Nursyahida Zulkifli; Rafizah Mohd Noor; `Ainatul Fathiyah Abdul Rahim; Nur Ain Yaacob; Nurul Afzan Najid (Journal of Islamic, Social, Economics and Development, 2023)
The emergence of gig economy was support by the rise of internet, the explosion of digital platform and mobile applications revolution that change the labour market and work pattern around the globe. Gig economy enable individual connect and transact through online platform such as Grab, Uber, Upwork, Fiverr and it allows workers to offer their services and expertise to a global audience, while clients could access a diverse range of services at the fingertips. People participation in the gig economy gained popularity in year 2020 since the Covid-19 pandemic hit and many got laid off. Gig economy offers advantages such as flexibility and a diverse range of opportunities, it also presents several challenges that impact workers' rights, economic security, and societal well-being. Therefore, this research comprehensively examines gig economy by conducting a bibliometric analysis. This study expanded all research from 2014 to 2021 by utilizing the similarities visualization software (Vosviewer). A sum of 355 publications were analysed as documented in the Scopus database in September 2021, identifying the most compelling subjects covered by the journal. Findings demonstrate several significant research concerns (gig economy, freelancer, social and economy) The research presents a roadmap for potential researchers, concentrating on critical areas where success is possible.